EVALUATION OF POTATO FOR THEIR RESISTANCE TO POTATO TUBERMOTH, PHTHORIMAEA OPERCULELLA (ZELLER) - Chandla, V. K.; Gopal, J.; Chandel, R S (Potato Journal, 2013)
In a laboratory test between 1996 to 2006 at the Central Potato Research Institute, Shimla, 1840 tuberosum and andigena accessions from germplasm were screened to determine the levels of resistance to attack by tubermoth, Phthorimaea operculella (Zell.). Of the germplasm tested CP 1644, CP2292, JEX/A 163, and JEX/A 250 were found tolerant.